Analisis Sistem Pemungutan Pajak Mineral Bukan Logam Dan Batuan Dalam Meningkatkan Pendapatan Asli Daerah Pada Badan Pendapatan Daerah Kabupaten Bengkalis - Ahmad Sahroni; Zakaria Batubara; Sukma Mehilda; Een Erlina (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This study aims to determine the system used by the Regional Income Agency in the collection of non-metallic mineral and rock tax in increasing the original income of the region, as well as to know the constraints in the implementation of the collection of Mineral Taxes instead of Metal and Bengkalis Regency Rocks. The type of research used in this study is qualitative with data collection techniques in the form of documentation, interviews, and literature study. The results of this study indicate that Bengkalis District Income Agency apply selfassessment system in the collection of Non-Metallic Mineral and Stone Taxes where taxpayers calculate, report and deposit / pay their own taxes to the Regional Regulatory Agency Bengkalis District. With the implementation of self assessment system in the collection of Non-Metallic Mineral and Stone Tax the taxpayers are encouraged to pay the taxes, so that each year the target of the Original Revenuerealized. From the data analysis of the target report on the realization of non-metallic mineral revenues and Bengkalis Regency's Rocks in 2014-2016 explained that the target of non-metallic mineral and mineral tax receipts every year reaches the set targets. However, revenue growth has decreased. Overall implementation of self assessment system in the collection of non-metallic mineral taxes and rocks at Bdan Revenue District Bengkalis is good, this is evidenced in the data target of realization of Non-Metallic Mineral and Stone Minerals reach the target set.